(3GdTchi h GdJfGRd YfgG (B: s (3OQGSI ebGQfI (B/ s - (3YHOGdMdje aDGO YHOGdMdje YHOGdMj Gdabjs; (3WGQb SQhQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2012)
(3GdbGYOI Cf GdfjGHI gj UGMHI GdGNJUGU GdCUjd aj QaY GdOYhi GdLfGFjI Yf cd LQjeI JbY Ohf Cf jQO Ydi SdWJgG aj gPG GdTCf bjO(B: (3ZjQ Cf GdeTQY bO NQL Ydi gPg GdbGYOI abjO SdWI GdfjGHI GdYGeI aj QaY GdOYhi GdLfGFjI GdfGTFI Yf HYV GdLQGFe GdJj JHOh ajgG ZdHI GdUGdM GdNGU Ydi GdUGdM GdYGe (B:(3h Pdc HJYdjb QaY gPg GdOYhi Ydi Tchi GdeLfj Ydjg GdPj jbOQ eG EPG cGf ef UGdMg JMQjc GdOYhi VO GdLGfj Ce ef GdCaVd GdSchJ YeG hbY efgs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFj, (B2012s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B462-483s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdOYhi GdLfGFjIs; (3GdTchis; (3GdVQQs; (3GdMb aj GdTchis; (3CWQGa GdTchis; (3GdLQGFe eMd GdTchis; (3BKGQ JbOje GdTchis; (3GfbVGA GdMb aj GdTchis; (3eGgjI GdJfGRd Yf GdTchi hBKGQgs; (3UGMH GdMb aj GdJfGRds; (3GdBKGQ GdCLQGFjI ddJfGRds; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs